Marketing Strategy in Improving Sales of Syar’i Clothing Azra Collection in Sidenreng Rappang Regency - Agustina, Vina Tri; Ramlan, Pratiwi; Yakub, Rahman (Journal of Management and Administration Provision, 2024)
The level of competition in the business world requires every seller to be able to carry out their marketing activities more effectively and efficiently. The purpose of this study is to determine how the marketing strategy of Azra Collection's sharia clothing increases sales, and to determine what factors influence the marketing of Azra Collection's sharia clothing. The population in this study were consumers of Azra Collection's sharia clothing store using the Accidental Sampling technique using the Slovin formula, so that 50 consumers were obtained as respondents. The research method uses quantitative research. Data collection techniques used in this study are using Observation, Literature Study, Interview, and Questionnaire techniques. The data analysis techniques used are simple linear regression coefficient analysis, t-test statistical analysis and F-test statistical analysis and processed using the SPSS application. The results of the study showed that marketing strategies had a significant effect on sales at the Azra store.